Adding scents to symbols: using food fragrances with deafblind young people making choices at mealtimes. (September 2014) - Murdoch, Heather; Gough, Anne; Boothroyd, Eileen; Williams, Kate
<x xml:space="preserve">Abstract</x> This article is written by Heather Murdoch, research consultant for the Seashell Trust, Anne Gough, deputy headteacher at Royal School Manchester/Seashell Trust, Eileen Boothroyd, consultant for the Seashell Trust, and Kate Williams, a creative perfumer for Seven (PZ Cussons). It describes the use of food fragrances with deafblind students who are making lunchtime meal choices. The fragrances were added to picture symbols or objects of reference used to represent different menu options. A multiple case study, mixed methods design was used to evaluate three students' choice‐making before and after the introduction of the fragrances. Case study was chosen because of the complex and diverse needs created by deafblindness and because the project was an exploratory study of a new approach. The methods included semi‐structured interviews with students' 1:1 keyworkers and other staff, direct and videotaped observations of students' choice‐making, and written diary records of students' food choices and responses. The findings are necessarily tentative but support the use of food fragrances to assist students' understanding of mealtime choice‐making and their engagement with the process. The practicalities of using olfaction to support other sensory inputs are discussed, together with priorities for future research and practice in this area.